A cluster of lysergic acid diethylamide (LSD) poisonings following insufflation of a white powder sold as cocaine. (2nd November 2021) - Roberts, Darren M.; Premachandra, Kulanka H.; Chan, Betty S.; Auld, Robin; Jiranantakan, Thanjira; Ewers, Christopher; McDonald, Catherine; Shaw, Vanessa; Brown, Jared A.
Abstract: Objective: Adulteration, substitution or contamination of illicit substances can have clinically significant implications when other illicit substances are included. Such circumstances can present as clusters of poisonings, including severe toxicity and death following exposure to unexpected illicit substances. We report a cluster of laboratory-confirmed lysergic acid diethylamide (LSD) in a powder that was sold as cocaine and used recreationally. Methods: The Prescription, Recreational and Illicit Substance Evaluation (PRISE) program established by the New South Wales Ministry of Health includes State-based hospital toxicology services, Poisons Information Centre, Forensic & Analytical Science Service and emergency services to identify clusters of severe and unusual toxicity associated with substance use. PRISE criteria include a known cluster (geographically or situationally related) of people with acute severe toxicity, especially when accompanied by a toxidrome that is inconsistent with the history of exposure. A timely comprehensive drug screen and quantification is performed in eligible cases and the results are related to the clinical features. The need for a public health response is then considered. Four individuals inhaled a white powder that was sold as cocaine and developed severe toxicity that was not consistent with cocaine which prompted transfer to hospital for further management. Results: LSD was confirmed in four subjects, and the concentrations in 3 of the individuals were 0.04–0.06 mg/L which are among the highest reported in the literature. Common clinical features were hallucinations, agitation, vomiting, sedation, hypertension, and mydriasis. One subject required intubation and admission to the intensive care unit, two required overnight admission, and the fourth was discharged following oral diazepam after observation. No subject suffered persistent injury. Conclusions: A close working relationship between pre-hospital emergency services, hospital-based clinical services, public health authorities, and analytical laboratories appears to be advantageous. Favourable clinical outcomes are observed from LSD poisoning despite high exposures with good supportive care.